Periodization Analysis of Bankruptcy Prediction at PT Matahari Department Store Tbk for the 2019–2024 Period - Indriyani, Siwi Nur; Irawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to determine and analyze bankruptcy predictions at PT. Matahari Department Store Tbk for the period of 2019-2024. This type of research is included in the quantitative descriptive research category. The research data source is the company's annual financial report data for the period of 2019 - 2024 which has been audited and can be accessed through the PT. Matahari Department Store Tbk. website: https://www.matahari.com/. The sampling technique used is purposive sampling. The analysis technique used in this study is the Altman Z-Score model using the ratio (Net Working Capital to Total Assets, Earnings Before Tax to Total Assets, Retained Earnings to Total Assets, Sales to Total Assets, and Total Equity to Total Assets) and the Grover model using the ratio (Working Capital to Total Assets and Earning Before Interest and Tax to Total Assets). The results of the analysis show that the model can adapt to the environment and economic conditions in Indonesia as an early warning system to mitigate the risk of bankruptcy in the future, so that management can immediately take preventive measures